Behavior of ternary blended cementitious rubberized mixes reinforced with recycled tires steel fibers under different types of impact loads. (November 2022) - Alsaif, Abdulaziz; Albidah, Abdulrahman; Abadel, Aref; Abbas, Husain; Almusallam, Tarek; Al-Salloum, Yousef
Abstract: This research primarily investigates the influence of incorporating steel fibers (recycled and manufactured) in Rubberized concrete (RuC) mixes on impact resistance. Impact resistance was comprehensively investigated for six steel fiber reinforced RuC (SFRRuC) mixes with a large volume of rubber, reaching a replacement of 40 % of fine and coarse aggregates. Besides mechanical properties, four different types of impact tests, including drop weight on concrete discs and prisms, rebound, and projectile impact, were performed. The impact results indicate that the incorporation of blended fibers in the RuC mixes substantially enhances the initial and failure impact energy of SFRRuC under drop weight tests on discs and prisms. The excellent impact performance was further confirmed by the results of the projectile impact test on concrete slabs, where the ejected mass as well as the crater sizes for the concrete slab containing 40 % rubber and steel fiber were the lowest, as the dual effect of rubber and steel fibers enhanced the ductility, toughness, and penetration resistance. Overall, the improved impact, flexural resistance and toughness index of SFRRuC compared to the plain concrete mix makes it a potential alternative and sustainable construction material for various applications including industrial floors and protective wall barriers in military structures.